2020
DOI: 10.3390/nu12103089
|View full text |Cite
|
Sign up to set email alerts
|

Daily Oral Administration of Protease-Treated Royal Jelly Protects Against Denervation-Induced Skeletal Muscle Atrophy

Abstract: Honeybees produce royal jelly (RJ) from their cephalic glands. Royal jelly is a source of nutrition for the queen honey bee throughout its lifespan and is also involved in fertility and longevity. Royal jelly has long been considered beneficial to human health. We recently observed that RJ delayed impairment of motor function during aging, affecting muscle fiber size. However, how RJ affects skeletal muscle metabolism and the functional component of RJ is as of yet unidentified. We demonstrate that feeding mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Among the enzymes and factors involved in apoptosis, caspase-3 degrades a variety of cytoplasmic and nuclear proteins and activates nucleases, which promote DNA degradation [ 53 ]. Thus, the detection of caspase-3 by immunocytochemistry assays has been used to identify and confirm cell death via apoptosis [ 54 ]. Since NSY-224(60) and WMTA did not change the number of Ki-67- and caspase-3-positive cells, both materials are considered to have no apoptotic effect and induce cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Among the enzymes and factors involved in apoptosis, caspase-3 degrades a variety of cytoplasmic and nuclear proteins and activates nucleases, which promote DNA degradation [ 53 ]. Thus, the detection of caspase-3 by immunocytochemistry assays has been used to identify and confirm cell death via apoptosis [ 54 ]. Since NSY-224(60) and WMTA did not change the number of Ki-67- and caspase-3-positive cells, both materials are considered to have no apoptotic effect and induce cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Royal jelly is rich in multiple fatty acids, such as trans-10-hydroxy-2-decenoic acid and 10-hydroxydecanoic acid. It attenuates denervation-induced skeletal muscle atrophy in C57BL/6J mice and stimulates myoblast proliferation and differentiation of C2C12 cells [81].…”
Section: Fatty Acidsmentioning
confidence: 96%
“…RJ removed protein (protease-treated RJ [pRJ]) also had a positive effect on skeletal muscle. Daily oral administration of pRJ prevents denervation-induced skeletal muscle atrophy [ 99 ], and it has been reported that pRJ affects muscle fiber thickness, expression of satellite cell catabolic gene, and proliferation and differentiation in C2C12 myoblasts [ 99 , 100 ].…”
Section: Natural Compounds (Effective Foods Against Denervation-induced Skeletal Muscle Atrophy)mentioning
confidence: 99%